Building a scalable data warehouse with data vault 2.0 - Linstedt, Daniel; Olschimke, Michael (Amsterdam : Morgan Kaufmann is an imprint of Elsevier, 2015)
Annotation This resource provides a complete introduction to data warehousing, applications and the business context so readers can get-up and running fast. It explains theoretical concepts and provides hands-on instruction on how to build and implement a data warehouse. In addition to demystifying data vault modelling with beginning, intermediate and advanced techniques, it discusses the advantages of the data vault approach over other techniques, as well as the latest updates to data vault 2.0 and multiple improvements to data vault 1.0.
3.3.1.4 -- Applying Six Sigma to Data Warehousing.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Data warehousing; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Data warehousing; Electronic books